The mechanism of LAMP2A-mediated exosome biogenesis and their role in intercellular communication - M Carvalho, Catarina (2023)
ABSTRACT Exosomes are a subtype of extracellular vesicles (EVs) of endocytic origin that have been the subject of intense research in the last 2 to 3 decades. Exosomes are part of a complex intercellular and inter-organ communication network, transporting and delivering nucleic acids, proteins and other biomolecules between cells. Exosomes have generated considerable interest as evidence demonstrate that they not only have paracrine and endocrine signalling capabilities, but also mediate cellular re-programming and multicellular coordination in several tissues and organs, participating in events such as the immune response, tumour progression and metastasis and neurodegeneration. However, we are still far from fully understanding the impact of exosomes in metazoans biology. Previously, we had described a mechanism for the loading of proteins into exosomes that relied in the lysosomal associated protein 2 isoform A (LAMP2A). This mechanism requires the presence, on the protein to be loaded, of a specific pentapeptide sequence, or ExoSignal, that is recognized by HSC70 in the cytosol and LAMP2A at the endosomal limiting membrane. With this work we now show that the exosomal Loading of Cargo (eLLoC) triages and loads proteins into a subpopulation of exosomes. This mechanism is ESCRT- independent and involves additional molecular players such as CD63, Syntenin-1, ALIX, RAB31 and the lipid ceramide. Furthermore, using the zebrafish as a model and by tagging fluorescent proteins with the ExoSignal we were able to follow inter-organ transfer of exosomes. Our findings identify eLLoC as a key mechanism in exosome biogenesis while in vitro and in the zebrafish, while providing new tools for exosome engineering in the pursuit for innovative therapeutic strategies.